Primer on multiple sclerosis - Giesser, Barbara S. (Oxford University Press, 2011)
Primer on Multiple Sclerosis was developed to provide a comprehensive overview of the clinical and basic science aspects of MS. It is designed to be of practical use to clinical neurologists, and addresses all of the major issues that may occur in the management of persons with MS. The reader is provided with the latest information on the science of MS, including immunology, genetics, epidemiology and pathology, as well as a summary of the newest directions in basic science research. Guidelines for diagnosis and appropriate use of diagnostic modalities are presented. All clinical aspects of MS.